Synthetic Approaches to Aryl Halomethyl Sulfones - M. Borys, Krzysztof; Ochal, Zbigniew (Current Organic Chemistry, 2016)
Aryl halomethyl sulfones are halogenated organosulfur compounds which continuously draw attention owing to their bioactivity as well as wide applications in organic synthesis. This review summarizes the methods for their preparation, describing the reported routes to fluoro, chloro, bromo and iodo derivatives. Their synthetic and biological applications are also highlighted.
Keywords: biocides